Steganographic Methods in Information Protection - Koziel, G. (Штучний інтелект, 2011)
New information protection methods are necessary. Steganography seems to be great opportunity to replace or supplement the cryptographic methods. Steganography gives additional possibilities. It allows to keep in secret the communication fact and communicating sites personality. A lot of existing methods and the proposal of a new one are presented in the article.